2015 edition of the Workshop of European Group for Intelligent Computing in Engineering (EG-ICE). (August 2017) - Beetz, Jakob; Hartmann, Timo
Abstract: In this Special Issue, four extended versions of selected contributions of the 2015 edition of the Workshop of European Group for Intelligent Computing in Engineering (EG-ICE) are presented. The selected papers span a variety of topics ranging from machine learning applications to weather forecast for potentially hazardous conditions affecting the built environment, topological optimization of Finite Element simulations of structural building components, the recognition of process patterns in construction schedules to the intelligent compression and efficient storage of large point cloud data sets. In their thematic heterogeneity, they are representative for the coverage of the annual workshops.